Dissertation on the Influence of Digital Innovations on the Financial Structure of SMEs of Uganda - Marc Julian Kirya (My University, 2023)
This study focuses on how digital innovations are reshaping the financial landscape for Small and Medium-sized Enterprises (SMEs) in Kampala, Uganda. It specifically looks at the adoption and impact of various digital tools, such as mobile money services, digital banking, fintech solutions, e-commerce, and debit/credit card payments, on SMEs' financial structures. The research findings indicate that mobile money services and digital banking are the most widely embraced digital innovations among the SMEs surveyed. These technologies provide SMEs with secure digital wallets, efficient transactions, remote accessibility, and cost savings. Mobile money, in particular, plays a significant role in promoting financial inclusion, allowing SMEs without traditional bank accounts to participate in the formal economy. However, the study also highlights several challenges that SMEs face in fully harnessing digital innovations. These challenges include limited digital literacy among business owners, infrastructure constraints, cyber-security concerns, regulatory uncertainties, and the digital divide between urban and rural areas. Overcoming these obstacles will be essential for SMEs to maximize the benefits of digital financial tools. In summary, while SMEs in Uganda are gradually integrating digital innovations into their financial operations, there is still room for growth in certain areas. Addressing the identified challenges and promoting digital financial literacy will be pivotal in helping SMEs leverage digital tools for improved financial management, expansion, and resilience in the evolving digital economy. Further research and targeted awareness campaigns are needed to facilitate this transition effectively.
This is a dissertation.